EFEKTIVITAS IMPLEMENTASI PROGRAM PELAJAR PANCASILA DI SDN 03 KOTO TANGAH KABUPATEN AGAM - Resi Darnalinda; Suciati; Rini Parmila Yanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research examines how the Pancasila Student Profile (PSP) is put into practice at SDN 03 Koto Tangah. The PSP, similar to the Character Education (PPK) framework from the 2013 curriculum, aims to nurture students who are lifelong learners. Its core purpose is to develop students with strong moral character, the ability to compete globally, sharp critical thinking skills, and innovative ideas, all in line with its established benchmarks. Specifically, this study looked at the degree to which the PSP was implemented at the school. Using a descriptive qualitative approach, the study was conducted at SDN 03 Koto Tangah. Primary data was collected from teachers, while secondary data came from students and the principal. Data was gathered through interviews, questionnaires, and documentation. The analysis involved reducing, presenting, and drawing conclusions from the data. The results showed that the PSP aspect averaged 72%, which was classified as